Reusable composite filter material and method of making and using the same to remove and destroy molecular contaminants in water

By using a technology of using a bonding material layer, a functionalized iron membrane and a hydrophobic coating in the composite filter material, the problem of difficulty in removing PFA molecules in water in the prior art is solved, efficient removal and safe treatment under mild conditions are achieved, and the filter material can be reused.

CN114502251BActive Publication Date: 2025-04-11COREWATER TECHNOLOGIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080070893.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-11
Filing Date
2020-10-10
Publication Date
2025-04-11
Estimated Expiration
2040-10-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove contaminants containing fluorine or fluorine-containing compounds, especially molecules of perfluoroalkyl and polyfluoroalkyl groups, such as PFOA and PFOS, and the harmful materials produced after treatment require harsh treatment conditions.

Method used

The composite filter material is used, and is made of a variety of basic filter materials through simple processes under mild conditions, including depositing a layer of adhesive material, a functionalized iron film and a hydrophobic coating on the surface of the granular activated carbon to achieve adsorption of pollutants and subsequent safe treatment.

Benefits of technology

It is achieved efficient removal of PFA molecules in water under mild conditions and releases pollutants into the treated effluent through a simple process, allowing safe discharge of pollutant-free effluents and reusable filter materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114502251B_ABST
    Figure CN114502251B_ABST
Patent Text Reader

Abstract

A specific functionalized composite filter material with a high specific surface area is used to adsorb PFA in drinking water. In a preferred embodiment, the base filter material is granular activated carbon (GAC), which is coated with a thin layer of polydopamine, a thin layer of partially oxidized iron, and a thin coating of octadecylamine in sequence. After PFA is adsorbed onto the coated GAC particles, the PFA is removed by a flushing process and retained in the flush effluent. The GAC particles are recovered and re-coated as needed to restore their adsorption capacity. The PFA-containing effluent is treated using a photochemical process to destroy the PFA molecules. The effluent that is now free of PFA can be treated as a harmless material. The composite filter material is suitable for systems ranging from small passive systems for personal use to large, high-flow utility water treatment systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to treating water by adsorption using composite adsorbents. The present invention more specifically relates to the removal of contaminants containing fluorine or fluorinated compounds. The present invention also relates to the regeneration of adsorbents / filters. In particular, the present invention relates to the removal of molecular contaminants from water and their safe destruction; in particular the removal and destruction of perfluoroalkyl and polyfluoroalkyl molecules, typically the long chain (C=8) molecules perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) and the related short chain PFAs (C≤7). Background Art

[0002] There is ample evidence that a variety of anthropogenic materials are now present in the environment and that their effects are persistent and harmful to human (and animal) life. Trace amounts of anthropogenic molecular substances (e.g., per- and polyfluoroalkyls, collectively referred to as PFAs) in drinking water are of particular concern. Two examples of methods for removing such molecular contaminants include: 1) passing the contaminated water through a bed of granular particles whose surfaces contain active sites for chemical adsorption and / or physical adsorption (physisorption); or 2) passing the contaminated water through a porous membrane, ultrafine mesh, or network of tightly packed fibers made of a variety of materials, all of which have active surface sites for chemical adsorption and / or physical adsorption. The effectiveness of either method depends on the number of active sites available to capture and hold the contaminant molecules, which in turn depends on the total surface area in contact with the water. An important fundamental filter material property is the ratio of surface area to mass of the material, or specific surface area, denoted as S. A , usually expressed in m 2 The unit is / g.

[0003] The higher the specific area of ​​the composite filter material, the less frequently the material needs to be replaced or (if possible) reactivated. There are two ways to achieve a high specific area for granular particles: in the case of solid particles, the diameter (or maximum dimension) is limited to a few microns or less, or a large number of nanoscale pores (from a few tenths of a nanometer to hundreds of nanometers) are created on the surface of each granular particle. An example of the former is a silica sphere of a few microns in diameter compared to a silica sphere of a millimeter or more in diameter. (For example, a silica sphere with a diameter of 1 mm has a specific area of ​​about 0.1 m 2 / g, while the specific area of ​​a sphere with a diameter of 10 microns is about 90m 2 / g. ) An example of the latter is a porous base filter material.

[0004] It is known to those experienced in the field of molecular contaminant adsorption that it is important to have a pore size distribution in the porous base filter material. Generally speaking, the closer the contaminant molecules are to the surface of the base filter element, the stronger the adsorption. In small diameter pores, the molecules will automatically move closer to the pore walls, making the adsorption stronger. Smaller, more strongly adsorbing pores are generally considered to have higher energy. A non-limiting example of a porous base filter material is granular activated carbon (GAC). Depending on the activation process, GAC can have a pore size as low as a few tenths of a micron. 2 / g to above 1500m 2 / g of specific surface area. The active surface sites are basically on the inner wall surface of the pores of the GAC particles. Generally, the pore size is generally divided into three major categories of size: micropores, which are less than two nanometers in size, usually a few nanometers to a few nanometers in this application; macropores, which are greater than 50 nanometers in size, usually a few nanometers to tens of nanometers in this application; and mesopores, which are 2 to 50 nanometers (inclusive), usually tens of nanometers to hundreds of nanometers in this application. The pores with higher energy are the micropores in the GAC particles. Mesopores are described in the art as a pathway for molecules to reach smaller pores, and are therefore expected to contribute less to the adsorption capacity of GAC than micropores and macropores.

[0005] While one common approach for treating drinking water containing molecular contaminants such as PFA is to use a bed of GAC, one difficulty with this approach is that once the GAC becomes saturated with, for example, PFA molecules, the GAC itself becomes a hazardous material and must be disposed of accordingly. Currently, there are two broad approaches to treating PFA-saturated granular activated carbon materials: 1) treat the spent GAC as a hazardous material so that the contaminants cannot escape from it and re-enter the environment; or 2) strip the contaminants from the GAC and incinerate them at very high temperatures. Typically such temperatures approach 1000C. Recent evidence now clearly indicates that extreme precautions must be taken to prevent the release of airborne PFA contaminants into the environment during incineration. A filter media specifically designed to eliminate the need for harsh treatment measures (such as a 1000C furnace) is clearly desirable. Summary of the invention

[0006] The present invention is a reusable composite filter material and a preparation method thereof, which can be made of a variety of basic filter materials using simple processes under mild conditions. Suitable basic filter materials include solid granular particles, porous granular particles, porous membranes, meshes, and solid or porous fibers that are bundled into a network. Usually, high-performance filter materials will have a high specific surface area and a large number of active surface sites. The improvement to this filter material is to pre-treat the filter material in such a way that once pollutant adsorption occurs, the gaseous base, solution base, or their combined treatment processes after adsorption will cause pollutants to be released from the filter material and enter the treatment effluent. The treatment effluent can then be directed to a suitable container, where it can be further processed to destroy pollutants, thereby allowing safe discharge of the effluent now free of pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 Depicted is a two-dimensional cross-sectional view of a portion of a three-dimensional particle (1) of granular activated carbon showing the openings (2) of an ideal array of pores resulting from the activation process. The surface of the three-dimensional particle (1) having pores (2) is then coated with polydopamine (PDA) (3) which is functionalized to improve its metal chelating ability. An iron film (4) is placed on the functionalized PDA and then an octadecylamine (ODA) film (5) is deposited. The smaller channels are micropores and the larger openings are mesopores leading to the micropores. The figure is not drawn to scale.

[0008] Figure 2 A flow chart showing the steps required to remove contaminants from water using composite filter materials. DETAILED DESCRIPTION

[0009] All embodiments of the present invention will capture a wide range of molecular contaminants from drinking water over a wide range of concentrations. As a non-limiting example, the expected concentration range of the PFA molecules extends from a few nanograms per liter to a few micrograms per liter. Again, without implying any limitation, the focus of the remaining paragraphs of this section will be on removing PFA molecules within the cited concentration range from drinking water. Two prominent examples of the PFA molecules are perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS). Without implying any limitation on the selection or configuration of the base (i.e., pretreatment) filter material, at least one embodiment of the base filter material is granular activated carbon. The pore width of the pretreated GAC can range from a few nanometers (nm) to greater than 100 nm. The first process step is to deposit a thin coating of a binding material on at least a portion of the GAC particles; the second step is to enhance the chelating ability of the binding material; the third step is to deposit a thin coating of at least partially oxidized metal on at least a portion of the functionalized binding material; and the fourth step is to deposit a hydrophobic coating on at least a portion of the oxidized metal coating. All coatings are deposited in a simple room temperature (or near room temperature) temperature process.

[0010] Since the present invention involves adding a coating to the pore surface that can close smaller micropores, it is important to have at least some macropores that will at worst become micropores after all the coating processes. The coating process may also result in some mesopores eventually becoming micropores and some macropores (if small enough) will also contribute to overall adsorption.

[0011] In one embodiment of the present invention, the functionalized adhesive material layer directly coated on the GAC surface comprises a functionalized polydopamine (PDA) layer. The thickness of the functionalized PDA layer is in the range of about a few tenths of a nanometer to about 5 nm. The second layer is an iron film deposited on at least a portion of the functionalized PDA layer. The iron film may be continuous or not continuous on the entire surface of the GAC, and may have a thickness ranging from a single layer to about 5 nm. At least a portion of the iron film is at least partially oxidized. The third layer comprises a hydrophobic material that covers the surface of the partially oxidized iron film in whole or in part, and (if present) may be a portion of any of the following: a non-oxidized iron film, a functionalized PDA coating, a PDA coating deposited as is, and an uncoated GAC substrate.

[0012] Other transition metals, alkali metals, alkaline earth metals, rare earth metals and all other metals of Groups 13, 14 and 15 of the Periodic Table of the Elements and their oxides, if any, may be used in place of or even in combination with iron.

[0013] All embodiments of the present invention will physically adsorb contaminant molecules over a wide range of concentrations in water. The physical adsorption (i.e., non-chemical adsorption) process is controlled by hydrophobic, electrostatic, or dispersion forces between the contaminant molecules and any given filter material. Adsorption of PFA molecules from water on surfaces with a surface charge close to zero but with a slight negative surface charge will occur primarily through hydrophobic forces. Similarly, if the surface has a near zero but slightly net positive charge, adsorption may be a combination of hydrophobic and weak electrostatic forces. It is generally believed that hydrophobic forces will dominate the physical adsorption of hydrophobic molecules on hydrophobic surfaces.

[0014] In one embodiment of the removal process, once the composite GAC particles have been saturated with PFA adsorbents, they can be placed in a solution designed to release the PFA adsorbent molecules from the composite GAC particles. When released into the treatment solution, the PFA adsorbent molecules can be carried away with the effluent, while the adsorbent substrate particles can be retained for reuse. In one embodiment of the present invention, the rinsed substrate particles can be restored to their original, uncoated surface. In another embodiment, the rinsed substrate particles can contain a coating of an adhesive catechol-based material on their surface. In another embodiment of the present invention, the rinsed substrate particles can contain a coating of an adhesive PDA material and a partially oxidized metal coating on the adhesive PDA coating. In another embodiment, the rinsed GAC substrate particles can contain a coating of an adhesive material, a metal coating, a partially oxidized metal coating, and a hydrophobic material coating. Once the hydrophobic coating and contaminant molecules are rinsed and removed, the GAC substrate particles can be reprocessed as needed to restore the material to its pre-adsorption configuration and reused.

[0015] The contaminated effluent from the filtration and flushing process can be treated using one of a variety of well-known photocatalytic processes. Non-limiting but illustrative, the flushing process effluent containing PFA adsorbate can be mixed with a volume of nanoscale photocatalytic particles, which include one or more metal oxides that promote the photocatalytic destruction of the PFA adsorbate molecules. The catalytic nanoparticles can have a maximum size in the range of about 5nm to 500nm. Depending on the electronic band gap of the photocatalytic particles, the wavelength of light that promotes the photocatalytic destruction of PFA contaminants can be in the range of about 650nm to about 100nm. Once the contaminant destruction is completed, the photocatalytic particles can be recovered by any suitable means (filtration, centrifugation, etc.) and the effluent discharged for treatment.

[0016] The method for preparing a reusable composite filter material as the subject of the present invention includes a series of sequential procedures, the details of which are provided below. Without limiting other substrates, the procedures described herein are applicable to GAC particles. Similar procedures can be used with other composite filter materials, whether in the form of granular properties or porous or non-porous membranes, ultrafine meshes or fiber networks (e.g., quartz wool fiber bundles). Procedure 1 provides process steps for preparing commercial granular activated carbon particles for the subsequent procedures described below. Procedures 2 and 3 provide two sets of optional process steps to deposit a coating of a bonding material on GAC. In a preferred embodiment, the bonding material is polydopamine (PDA). Procedure 4 provides a process step for modifying (i.e., functionalizing) the PDA membrane to produce dihydroxyindole (DHI) subunits on its surface to increase its metal chelating ability. Procedure 5 provides a process step for coating a functionalized PDA surface with an at least partially oxidized iron film. Procedure 6 provides a process step for applying a hydrophobic coating of octadecylamine (ODA) to an at least partially oxidized metal coating as the final layer on the GAC particles. The ODA coating is exemplary and not limiting as other hydrophobic coatings may be used with other suitable process steps not included herein.

[0017] Unless otherwise stated, all procedures were performed at room temperature.

[0018] By way of example and not limitation, once the composite functionalized GAC particles have adsorbed a predetermined mass of PFA molecules, the adsorbed PFA molecules can be removed from the GAC by removing the hydrophobic layer as described in Procedure 7. If desired, the iron film can then be removed from the particles by following the process steps in Procedure 8. The resulting effluent can be added to the rinse effluent from Procedure 7. The PFA molecules contained in the effluent from the rinse procedure are then denatured or destroyed by applying the process steps provided in Procedure 9.

[0019] The particle adsorption capacity and the total amount of PFA molecules adsorbed under a given set of conditions can be determined by following the process steps provided in Procedure 10.

[0020] The particles, procedures for making and using the particles, and contaminants described as targets for adsorption are illustrative and not limiting.Alternatives to the techniques described herein will be known to those skilled in the art of depositing and removing materials on surfaces.

[0021] Procedure 1: Sorting and cleaning of received coal-based or plant-based granular activated carbon particles

[0022] Materials used:

[0023] -Specific surface area greater than 900m 2 / g of granular activated carbon (GAC) particles

[0024] -150ml-300ml deionized (DI) water

[0025] -Nitrogen

[0026] Process steps:

[0027] - Weigh 10-20 g of the received granules.

[0028] - As an illustration and for one specific embodiment, screen and retain only 2.36 mm (#8 screen) to 2.8 mm (#7 screen) GAC.

[0029] - Remove dust with compressed air.

[0030] - Rinse the pellets with 150ml-300ml DI water.

[0031] - Dry with a low pressure nitrogen stream.

[0032] -Bake at 125C overnight.

[0033] Procedure 2: Deposition of a thin coating of a binder catechol-based material from an alkaline solution (pH = 8.5) on granular activated carbon particles layer

[0034] Materials used:

[0035] -2g GAC sorted and cleaned according to procedure 1 above

[0036] -250ml 8.5pH Tris base

[0037] -0.4g dopamine hydrochloride

[0038] Process steps:

[0039] - Combine 2 g of particles with 250 ml Tris and 0.4 g dopamine in a 1000 ml Erlenmeyer flask.

[0040] - Aerate and shake at 125 rpm for 2 hours.

[0041] - Rinse with 100ml DI water.

[0042] - Dry the sample at 70C for 16-24 hours.

[0043] - Re-weigh.

[0044] Procedure 3: Deposition of acid-based binder catechol-based material on granular activated carbon particles

[0045] Materials used:

[0046] - 1g GAC sorted and cleaned according to procedure 1 above

[0047] -250ml McIlvaine buffer pH 5

[0048] -0.4g dopamine hydrochloride

[0049] -0.01g sodium periodate

[0050] Process steps:

[0051] - Combine 1 g GAC with 250 ml McIlvaine buffer and 0.4 g dopamine in a 1000 ml Erlenmeyer flask.

[0052] - Add sodium periodate, vortex, aerate and shake at 125 rpm for 2 hours.

[0053] - Rinse the pellets with approximately 40 ml of DI water.

[0054] - Stir in 150 ml DI water at 250 rpm for 60 minutes.

[0055] - Rinse the pellets with 100 ml of DI water.

[0056] - Dry the sample at 70C for 16-24 hours.

[0057] - Re-weigh.

[0058] Procedure 4: Functionalization of the PDA layer on the GAC substrate particles to generate dihydroxyindole on the PDA surface (DHI) subunit

[0059] Materials used:

[0060] -33.29g CaCl2

[0061] -6.05g Tris buffer

[0062] -1L DI H2O

[0063] -1g of polydopamine-coated granules

[0064] -HCl

[0065] Process steps:

[0066] - Prepare CaCl2 and Tris solution by combining 33.29 g CaCl2 and 6.05 g Tris in 1 L DI H2O.

[0067] - Adjust pH to 9.5.

[0068] - Combine in the following proportions: 1 g of granules to 100 ml of treatment solution.

[0069] - Bubble air through the solution for 4 hours and mix with a stir bar.

[0070] - Remove the pellet from the solution and rinse with 200 ml DI H2O.

[0071] - Incubate the particles in pH 2.5 HCl for 15 minutes.

[0072] - Remove the pellet from the solution and rinse with 200 ml DI H2O.

[0073] Procedure 5: Deposition of an at least partially oxidized iron film on a functionalized PDA layer on a GAC ​​substrate particle - Ferrous chloride process art

[0074] Materials used:

[0075] -0.01g FeCl2

[0076] -5g PDA@GAC

[0077] -1ml NaClO

[0078] -HC1

[0079] -NaOH

[0080] -Vibration table

[0081] -pH meter

[0082] Process steps:

[0083] - In a 50 ml flask, combine FeCl2 with 25 ml DI water with up to 5 g PDA@GAC per 25 ml.

[0084] - Shake at >160 rpm for 2 hours.

[0085] -After 2 hours, insert the pH meter and take a reading.

[0086] - Add 1 ml NaClO.

[0087] - Once stable, adjust the pH to about pH 5.0 with NaOH solution (or HCl if necessary).

[0088] -Continue vibrating.

[0089] - Repeat steps 2-6 three more times (using a total of 4 ml NaClO).

[0090] - Rinse twice with 200 ml DI H2O.

[0091] - Dry the finished granules at 80C for minimum 4 hours before use.

[0092] Procedure 6: Deposition of metal oxide layer on adhesive catechol based substrate on Al2O3 or GAC porous granular substrate Octadecylamine (ODA) thin layer-chloroform process

[0093] Materials used:

[0094] -100ml chloroform

[0095] -0.4g octadecylamine

[0096] -1.0g composite particles for coating

[0097] Process steps:

[0098] - Add 100 ml of chloroform to a suitable beaker.

[0099] - Add 0.4 g of octadecylamine to chloroform.

[0100] - Add 1.0 g of composite particles to be coated.

[0101] - Shake the mixture for the desired time (5 min - 2 h).

[0102] - Use a stainless steel mesh to filter out particles.

[0103] - Dry granules, not exceeding 60C.

[0104] Procedure 7: Removal of the octadecylamine (ODA) layer containing PFA molecules after adsorption

[0105] Materials used:

[0106] -100ml DI H2O

[0107] - Up to 5g of contaminated particles

[0108] -Hot Plate

[0109] Process steps:

[0110] -Add DI H2O to a beaker and heat to 80C on a hot plate.

[0111] -Add the contaminated particles to the beaker and cover it.

[0112] - Heat for up to 1 day.

[0113] - Filter out particles from waste streams.

[0114] - Test the PFA content of the wastewater according to EPA Circular 537.1.

[0115] Procedure 8: Dissolution of previously deposited iron from adsorbent particles after removal of ODA / PFA

[0116] Materials used:

[0117] -0.5g intact GAC granules retained from procedure 6

[0118] -50ml 5% nitric acid

[0119] Process Steps: Important: Perform all work in a fume hood.

[0120] - 0.5 g of the previously prepared adsorbent particles were placed in 50 ml of 5% nitric acid preheated to 70°C.

[0121] - Shake on a shaker at 125-400 rpm for 15 minutes.

[0122] - Remove GAC particles from the solution by filtering through a Nalgene filter.

[0123] - Test the filtrate for iron concentration.

[0124] - Rinse the pellet and save the effluent for analysis.

[0125] - Test the PFA content of the wastewater according to EPA Circular 537.1.

[0126] - Test the rinse effluent for iron content using any convenient standard technique such as atomic adsorption spectroscopy.

[0127] Procedure 9: Photocatalytic destruction of PFOS and PFOA and related PFA compounds using combined metal oxide nanoparticles thing

[0128] Materials Needed:

[0129] -0.1g Fe2O3@TiO2 composite nanoparticles, approximate average maximum size ranging from 20nm to 60nm

[0130] - Acid-resistant photocatalytic reaction chamber with a total volume of 350ml

[0131] -Quartz jacketed UV-C light source (6W, 120v)

[0132] - 300 ml of filtrate and rinse effluent from procedures 7 and 8

[0133] -Micro orbital shaker

[0134] Process steps

[0135] - Pour 300 ml of rinse effluent into the reaction chamber.

[0136] - Add 0.1 g of composite dry nanoparticles into the chamber.

[0137] -Seal the chamber and place on a shaker at 200-450 rpm.

[0138] - Turn on the UV light and allow the reaction to proceed for at least 24 hours.

[0139] -Removing the solution from the reaction chamber.

[0140] - Allow the solution to settle and then pour off as much liquid as possible for the PFA test without pouring off any nanoparticles. If necessary, centrifuge the solution to obtain maximum nanoparticle retention.

[0141] Procedure 10: Photocatalytic Decomposition of PFOA, PFOS and Related PFA Compounds Using Single Oxide Nanoparticles bad

[0142] Materials Needed:

[0143] -0.1 Approximate average maximum size of TiO2 nanoparticles in the range of 5nm to 60nm

[0144] - Acid-resistant photocatalytic reaction chamber with a total volume of 350ml

[0145] -Quartz jacketed UV-C light source (6W, 120v)

[0146] -300 ml of filtrate and rinse effluent from procedures 7 and 8

[0147] -Micro orbital shaker

[0148] Process steps:

[0149] - Pour 300 ml of filtrate and rinse effluent into the reaction chamber.

[0150] - Add 0.1 g of dry nanoparticles into the chamber.

[0151] - Sealed chamber, placed on a shaker at 200-450 rpm.

[0152] - Turn on the UV light and allow the reaction to proceed for at least 24 hours.

[0153] -Removing the solution from the reaction chamber.

[0154] - Pour off as much liquid as possible for the PFA test without pouring off any nanoparticles. If necessary, centrifuge the solution to obtain maximum nanoparticle retention.

[0155] The rinsed separated, now contaminant-free adsorbent particles obtained from Procedures 7 and 8 may be re-functionalized by an appropriate method or combination of methods described in Application Procedures 1-6.

[0156] Once any of the embodiments of the present invention have been produced, they can be tested for adsorption capacity using the following procedure 11.

[0157] Procedure 11: Testing the composite filter material for PFOS and PFOA adsorption

[0158] Materials Needed:

[0159] - Several grams of prepared composite filter material

[0160] - Prepare multiple amounts of DI water containing PFOS and PFOA at specified concentrations ranging from about 1 ppb each to about 100 ppb each

[0161] Process steps:

[0162] - To each of multiple Erlenmeyer flasks containing at least 100 ml of prepared contaminated DI water, an amount ranging from 1 g to 10 g of the composite filter material was added.

[0163] - Place the flask on an orbital shaker for 24 hours at a speed sufficient to promote mixing of the composite filter material and contaminants.

[0164] - Decant the liquid and analyze for PFA according to EPA Circular 537.1 PFA test procedure.

[0165] All embodiments of the present invention formed using the above or similar procedures are suitable for adsorbing contaminant PFA molecules from water. Adsorption can be accomplished by: 1) placing the composite filter material in a fixed filter bed and allowing the contaminated water to flow through the bed; or 2) mixing the composite filter material directly with the contaminated water for a predetermined time and then separating the composite filter material from the water by, for example, centrifugation, simple sieving or other suitable processes.

[0166] By way of illustration and not limitation, at least one sample of the composite GAC particles disclosed herein was tested for adsorption capacity as follows: capacity to adsorb PFOA: 2.99 mg / g, and adsorption of PFOS: 2.43 mg / g. For comparison, the original GAC from the same batch of material was tested after Procedure 1 as follows: PFOA: 2.86 mg / g; PFOS: 2.30 mg / g. The results show that the particles embodying the present invention are as effective as the original particles in adsorbing PFA. The significant difference is that the PFA molecules adsorbed by the original GAC particles can only be removed under harsh conditions, while the present invention enables such removal under mild conditions and by a simple process.

[0167] In one embodiment of the present invention, PFA molecules were removed from composite GAC particles by applying the process described in step 7 to the composite GAC particles used in the typical adsorption test described previously. The amount of PFOA adsorbed from 50 ml of contaminated water by 0.5 g of the composite GAC preparation using Procedure 11 was determined to be 14 ± 1.5 micrograms. The amount of PFOA recovered in 50 ml of initial clean water using Procedure 7 was determined to be 12 ± 0.8 micrograms according to EPA Circular 537.1, which is consistent with the initial adsorption amount within the experimental error noted.

Claims

1. A composite filter material for removing contaminants from water, wherein the composite filter material is composed of a base filter material having a surface area, the base filter material comprising one of solid granular particles, porous granular particles, porous membranes, ultrafine meshes, or a network of solid or porous fibers; and wherein the surface area of ​​the base filter material is at least partially coated with a thin layer of a binding material, the thin layer of binding material comprising polydopamine; wherein the thin layer of adhesive material is at least partially coated with a thin layer of metal, the thin layer of metal comprising iron; wherein the metal thin layer is at least partially oxidized, such that the metal thin layer comprises at least partially oxidized iron; and The partially oxidized metal thin layer is at least partially coated with a hydrophobic material thin layer, wherein the hydrophobic material thin layer comprises octadecylamine.

2. The composite filter material of claim 1, wherein the porous granular particles are granular activated carbon.

3. The composite filter material of claim 2, wherein the porous granular particles are microporous.

4. The composite filter material of claim 2, wherein the porous granular particles are macroporous.

5. The composite filter material of claim 2, wherein the porous granular particles are mesoporous.

6. The composite filter material according to claim 2, wherein the granular activated carbon contains three types of pores: micropores, mesopores, and macropores.

7. A method for removing and treating perfluoroalkyl and polyfluoroalkyl substances from water, the method comprising the steps of: placing a certain amount of the composite filter material of claim 1 in contaminated water, and leaving the composite filter material in the mixture of the contaminated water and the composite filter material for a period of time; and removing the composite filter material from the mixture; and placing the composite filter material in clean water to prepare a second mixture, heating the second mixture, and maintaining the second mixture at 80° C. for 1 day; and removing the composite filter material from the mixture to leave an effluent; and placing the effluent from the second mixture in a photocatalytic reaction chamber having any one of titanium dioxide@iron oxide nanoparticles or titanium dioxide nanoparticles and a UV light source, and sealing; and Turning on the UV light source and vibrating the photocatalytic reaction chamber at 250 to 400 RPM for at least 24 hours; and The recovered composite filter material is placed in a suitable storage medium for future processing as needed.

Citation Information

Patent Citations

  • Method for degrading PFOA (perfluorooctanoic acid) in water by using Pt-doped In2O3 photocatalysis

    CN106219666A

  • Activated carbon, method for producing the same, and water-purifying device

    JP2003261314A

  • Hydrophobic adsorbent and method of producing the same

    JP2013103174A